2015
DOI: 10.1038/srep07821
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh approximation to ground state of the Bose and Coulomb glasses

Abstract: Glasses are rigid systems in which competing interactions prevent simultaneous minimization of local energies. This leads to frustration and highly degenerate ground states the nature and properties of which are still far from being thoroughly understood. We report an analytical approach based on the method of functional equations that allows us to construct the Rayleigh approximation to the ground state of a two-dimensional (2D) random Coulomb system with logarithmic interactions. We realize a model for 2D Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The XRD diffractogram of the DPP‐Ful film (Figure ) show peaks at 2 θ =5.07° and 4.37°, corresponding to an inter‐plane spacing of 1.74 nm and 2.02 nm, respectively. The inter‐plane spacing of 1.74 nm in DPP‐Ful is higher than the inter‐plane spacing of 1.4–1.5 nm of pure DPP, observed in previous studies and similar to 1.78–2.07 nm for DPP blended with PCBM . The peak at 1.97° corresponds to an in‐plane spacing of 4.48 nm, which is also close to the molecular length of DPP‐Ful.…”
Section: Methodssupporting
confidence: 75%
“…The XRD diffractogram of the DPP‐Ful film (Figure ) show peaks at 2 θ =5.07° and 4.37°, corresponding to an inter‐plane spacing of 1.74 nm and 2.02 nm, respectively. The inter‐plane spacing of 1.74 nm in DPP‐Ful is higher than the inter‐plane spacing of 1.4–1.5 nm of pure DPP, observed in previous studies and similar to 1.78–2.07 nm for DPP blended with PCBM . The peak at 1.97° corresponds to an in‐plane spacing of 4.48 nm, which is also close to the molecular length of DPP‐Ful.…”
Section: Methodssupporting
confidence: 75%
“…It has been reported that DPP core molecules end-capped with p-stacking moieties exhibited PCE between 4 and 5.3% when blended with different fullerene derivatives such as phenyl-C 71 -butyric acid methyl ester 36 and methano indene fullerene in BHJ OPV cells. 37 The strong electron-withdrawing nature of DPP makes it possible to be exploited as an n-type organic semiconductor. 7,26 Jung and Jo reported a non-fullerene molecular acceptor composed of DPP and benzothiadiazole with a PCE of 5.0% when combined with thieno [3,4-b]thiophene/benzodithiophene (PTB7) as an electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…This theory uses the fundamental notion of the representative volume element (RVE) introduced in [44,45]. A simple algorithm was proposed in [46,47] and was complemented by computer simulations [48,49] to describe composites by the macroscopic behaviour based on the locations of inclusions and their sizes. It was established in [45] that the effective property tensors of fibre-reinforced composites have the form of double series on the concentration of inclusions and on "basic elements" which depend only on locations of the inclusions.…”
Section: Rve Theorymentioning
confidence: 99%